Affordable housing policies in the United Kingdom and their lessons for Developing Asia. - Sharma, Manoj; Kim, Sung Su; Sonn, Jung Won (ADB Briefs., 2021)
Rapid urbanization fueled by economic growth is widely seen as the fundamental cause of housing unaffordability in developing Asian cities. This brief analyzes the United Kingdom policies to address housing affordability issues and identifies which might be most relevant for developing Asia. It suggests that the country rental financing mechanisms, land provision schemes, and the role of housing associations in efficiently building and maintaining affordable housing are worth further exploration.